1951
DOI: 10.1042/bj0500182
|View full text |Cite
|
Sign up to set email alerts
|

Tissue fractionation studies. 2. The nature of the linkage between acid phosphatase and mitochondria in rat-liver tissue

Abstract: In the preceding paper , the existence in rat-liver tissue of a mitochondrialinked form of acid phosphatase has been described and the cytological significance of this finding has been discussed. The nature of the linkage between enzyme and granule forms the object of the present communication.Two facts relevant to this problem have already been reported, namely the great lability of the complex, which can be disrupted quantitatively by mechanical or physical means (Waring blender, freezing and thawing, hypoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1

Year Published

1952
1952
2008
2008

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(25 citation statements)
references
References 2 publications
4
20
1
Order By: Relevance
“…For the measurement of free activities, the substrate mixtures were made up so as to realize the assay conditions described by and by de Duve, Pressman, Gianetto, Wattiaux & Appelmans (1955); they contained in addition all the components of low molecular weight present in the pre-incubation medium. As observed before (Berthet, Berthet, Appelmans & de Duve, 1951) and again here in some preliminary experiments, lack of the last-named precaution may be responsible for the osmotic rupture of the particles, if they are permeable to one or more of the omitted components. The methods used for stopping the reactions and performing the subsequent analyses were those described previously .…”
Section: Methodssupporting
confidence: 76%
See 2 more Smart Citations
“…For the measurement of free activities, the substrate mixtures were made up so as to realize the assay conditions described by and by de Duve, Pressman, Gianetto, Wattiaux & Appelmans (1955); they contained in addition all the components of low molecular weight present in the pre-incubation medium. As observed before (Berthet, Berthet, Appelmans & de Duve, 1951) and again here in some preliminary experiments, lack of the last-named precaution may be responsible for the osmotic rupture of the particles, if they are permeable to one or more of the omitted components. The methods used for stopping the reactions and performing the subsequent analyses were those described previously .…”
Section: Methodssupporting
confidence: 76%
“…Such a role has been suspected before on the basis of temperature and pH effects (Berthet et al 1951; Table 2. Influence of lecithina8e on 8olubility of ly8osomal hydrola8e8 A mitochondrial preparation was pre-incubated for 10 min.…”
Section: Thernal Activationmentioning
confidence: 82%
See 1 more Smart Citation
“…Favoring this view is the fact that the presence of sucrose decreases additional histamine release by NaCI from the mast cell precipitates (3,000g) after application of compound 48/80. These results and the observation of Berthet and others (14) that the release of enzyme by NaCI from liver lysosomes was inhibited by sucrose, indicate that sucrose prevents the release of various substances from subcellular granules, although this mechanism remains unexplained.…”
Section: Methodssupporting
confidence: 56%
“…It has been suggested (1) that these granules may be related to "secretory granules" and "Golgi bodies" and to fractions rich in add phosphatase which had been isolated from the cells of the liver of the rat by Palade (3), Novikoff, Podber, Ryan, and Noe (4), and Berthet el al. (5). De Duve et al (6) have shown recently that this liver fraction is distinct from the mitochondrial fraction and that acid phosphatase, ~-glucuronidase, ribonuclease, desoxyribonudease, and cathepsin are concentrated in it.…”
mentioning
confidence: 99%